Efektifitas Penggunaan Aplikasi Canva dalam Pembuatan Materi Ajar oleh Guru di Sekolah SMK Negeri 1 Tondano - Imam, Indra A.; Diange, Sulis; Pangalila, Theodorus (CV. Kurnia Grup, 2024)
This research aims to evaluate the effectiveness of using the Canva application in creating teaching materials by the teacher at SMK Negeri 1 Tondano. Using a descriptive approach, this research involved PPKN teachers and students as research subjects. Research stages include planning, implementation, and monitoring and evaluation. The research results showed that the training in making teaching modules using Canva at SMK Negeri 1 Tondano was successful in involving teachers subject from various fields. Thorough preparation allows participants to quickly understand how to use Canva. Hands-on practice sessions help teachers create interesting teaching modules, although some modules require revision. Evaluation of participants' understanding through questionnaires also showed positive results regarding the implementation of the skills learned. It is hoped that this research can contribute to the development of innovative technology-based learning methods at SMK Negeri 1 Tondano, as well as enriching the literature regarding the use of technology in education in Indonesia.